Adenoviral Vector-Based Vaccine Expressing Hemagglutinin Stem Region with Autophagy-Inducing Peptide Confers Cross-Protection Against Group 1 and 2 Influenza A Viruses - Wen-Chien Wang; Ekramy E. Sayedahmed; Marwa Alhashimi; Ahmed Elkashif; Vivek Gairola; Muralimanohara S. T. Murala; Suryaprakash Sambhara; Suresh K. Mittal (Vaccines)
Background/Objectives: An effective universal influenza vaccine is urgently needed to overcome the limitations of current seasonal influenza vaccines, which are ineffective against mismatched strains and unable to protect against pandemic influenza. Methods: In this study, bovine and human adenoviral vector-based vaccine platforms were utilized to express various combinations of antigens. These included the H5N1 hemagglutinin (HA) stem region or HA2, the extracellular domain of matrix protein 2 of influenza A virus, HA signal peptide (SP), trimerization domain, excretory peptide, and the autophagy-inducing peptide C5 (AIP-C5). The goal was to identify the optimal combination for enhanced immune responses and cross-protection. Mice were immunized using a prime-boost strategy with heterologous adenoviral (Ad) vectors. Results: The heterologous Ad vectors induced robust HA stem-specific humoral and cellular immune responses in the immunized mice. Among the tested combinations, Ad vectors expressing SP + HA stem + AIP-C5 conferred significant protection against group 1 (H1N1 and H5N1) and group 2 (H3N2) influenza A viruses. This protection was demonstrated by lower lung viral titers and reduced morbidity and mortality. Conclusions: The findings support further investigation of heterologous Ad vaccine platforms expressing SP + HA stem + AIP-C5. This combination shows promise as a potential universal influenza vaccine, providing broader protection against influenza A viruses.